Influence of Mycosphaerella and Teratosphaeria leaf diseases on chemical composition of essential oils of Eucalyptus globulus and effect of these essential oils on ascospores germination - Passador, Martha Maria; Marubayashi, Julio Massaharu [UNESP]; Uzzo, Roberta Pierry; Marques, Marcia Ortiz Mayo; Conceição, Danila Monte; da Silva Marques, Ana Paula [UNESP]; Furtado, Edson Luiz [UNESP] (Springer Nature, 2021)
In a first step, essential oils were extracted from Eucalyptus globulus leaves, healthy and with symptoms and signs of Mycosphaerella leaf disease (MLD) and Teratosphaeria leaf disease (TLD), in two leaf stages. Stage 1: sessile, oval leaves covered by a waxy layer of a bluish colour, with opposite phyllotaxis, inserted along stems of quadrangular section. Stage 2: narrow and sickle leaves with a greyish green surface, mainly on the abaxial surface, inserted in alternating pairs along rounded stems. The essential oils were extracted by hydrodistillation and were analyzed by gas chromatography coupled with mass spectrometry. Chemical composition data and percentages of essential oil constituents were submitted to cluster analysis and principal component analysis. In a second step, under in vitro conditions, was evaluated the germination of Teratosphaeria nubilosa (one of the causal agents of TLD) ascospores in contact with the four types of essential oils extracted. The evaluations were performed at 24, 48 and 72 h after the experiments were assembled. The present study made it possible to distinguish and identify the chemical composition of essential oils from the eucalypt leaves used, and allowed 1,8-cineole to be identified as the major component for the essential oils investigated. The contact between essential oils and T. nubilosa spores allowed to prove the inhibition of the ascospores germination, being more efficient for the essential oils extracted from materials with the disease, which presented high amounts of 1,8-cineole.
Keywords: Essential oil; Eucalyptus globulus; Host–pathogen interactions; Leaf disease